Autoimmune pancreatitis in MRL/Mp mice is a T cell-mediated disease responsive to cyclosporine A and rapamycin treatment. Issue 3 (5th April 2013) - Schwaiger, Theresa; van den Brandt, Cindy; Fitzner, Brit; Zaatreh, Sarah; Kraatz, Franziska; Dummer, Annegret; Nizze, Horst; Evert, Matthias; Bröker, Barbara M; Brunner-Weinzierl, Monika C; Wartmann, Thomas; Salem, Tareq; et al.
Abstract : Background: Autoimmune pancreatitis (AIP) in humans invariably responds to steroid treatment, but little is known about the underlying pathogenesis and the benefits of alternative treatments. Objective: To study the pathogenesis, and the efficacy of alternative immunosuppressant agents in the MRL/Mp mouse model of AIP. Design: MRL/Mp mice were pretreated for 4 weeks with polyinosinic:polycytidylic acid to induce AIP. Pancreatic sections of mice genetically deleted for CTLA-4 were analysed. Blockage of CTLA-4 was achieved by intraperitoneal antibody treatment with 2 μg/g anti-mouse-CD152. Subsequent therapeutic studies were performed for a period of 4 weeks using cyclosporine A (40 μg/g), rapamycin (1 μg/g) or azathioprine (15 μg/g). Results: Blockage of CTLA-4 in MRL/Mp mice suppressed regulatory T cell (Treg) function and raised the effector T cell (Teff) response with subsequent histomorphological organ destruction, indicating that AIP is a T cell-driven disease. Using an established histopathological score, we found that dexamethasone, cyclosporine A and rapamycin, but less so azathioprine, reduced pancreatic damage. However, the beneficial effects of cyclosporine A and rapamycin were achieved via different mechanisms: cyclosporine A inhibited Teff activation and proliferation whereas rapamycin led to selective expansion of Tregs which subsequently suppressed the Teff response. Conclusions: The calcineurin inhibitor cyclosporine A and the mammalian target of rapamycin (mTOR) inhibitor, rapamycin, improve the course of AIP in MRL/Mp mice via different mechanisms. These findings further support the concept of autoreactive T cells as key players in the pathogenesis of AIP and suggest that cyclosporine A and rapamycin should be considered for treatment of AIP in humans.